Estudio de desempeño de distintos perﬁles de álabe de una turbina eólica para aprovechar vientos de baja velocidad - Gallo Jaramillo, Luis Antonio; Chica Arrieta, Edwin Lenin; Flórez Serrano, Elkin Gregorio (Ingeniería, 2022)
Context: Vertical-axis wind turbines, and Savonius-type turbines in particular, outstrip other types of turbines in applications that include erratic and low-speed winds. Although their efficiency is among the lowest, this can be compensated by their low cost, turning them into a sustainable alternative which is also appealing for this type of applications. This research seeks to select the highest-performance geometry for the blade of a Savonius-type wind turbine. Method: To this effect, various geometric configurations used in this type of turbines, which were consulted in the literature, are numerically analyzed. All the profile models are studied under the same computational fluid dynamics parameters and models through the ANSYS Fluent software. Results: Through computational simulations, the optimal performance conditions of each of the geometries are estimated. These conditions allow comparing the performance of the profiles under the same terms, as well as identifying the ones with the highest performance. It is determined that the conventional semicircular profile and the one known as the modified Bach have power coefficients of 0,287 and 0,395, respectively, which represents a performance increase of 37,8%. Conclusions: These superior results motivate a detailed analysis of the modified Bach profile which allows finding the optimal geometric proportions for its aerodynamic performance.